2022
DOI: 10.1038/s41391-022-00597-4
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol and prostate cancer survival in a Finnish population-based cohort

Abstract: Background Allopurinol is gout medication that inhibits uric acid formation. Its possible anti-carcinogenic properties have been under research in past years. Studies based on Taiwanese registries showed that long term allopurinol use might reduce prostate cancer (PCa) incidence. However, our studies based on Finnish registries did not support those findings. In this study, we evaluate whether allopurinol use is associated with prostate cancer-specific survival (CSS) or overall survival (OS) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Other different and very useful factors in the development of interventions regarding oncometabolites related with prostate cancer are choline [26], glucose [10], nitric oxide [27] and uric acid [28]. Although these oncometabolites seem related with the severity and mortality in patients suffering from prostate cancer, interventions reducing the presence of for instance uric acid do not show a significant reduction in tumor growth or overall survival [29]. These results show the difficulty in understanding the way cancer cells use oncometabolites to proliferate and progress, making the interpretation of metabolomics essential.…”
Section: Introductionmentioning
confidence: 99%
“…Other different and very useful factors in the development of interventions regarding oncometabolites related with prostate cancer are choline [26], glucose [10], nitric oxide [27] and uric acid [28]. Although these oncometabolites seem related with the severity and mortality in patients suffering from prostate cancer, interventions reducing the presence of for instance uric acid do not show a significant reduction in tumor growth or overall survival [29]. These results show the difficulty in understanding the way cancer cells use oncometabolites to proliferate and progress, making the interpretation of metabolomics essential.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that gout may be associated with prostate cancer [9][10][11]. One study even identified a potential mechanism of the relationship between gout and prostate cancer demonstrating that a change in plasma or intracellular urate levels has an impact on prostate cancer cell growth [12]. This indicated that the use of uric acid-lowering agents, such as Allopurinol, would potentially be therapeutic in the prevention of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%